Internalisasi Nilai-Nilai Adab Makan dan Minum Melalui Animasi Kartun Islami Di RA El Syarifah Medan - Syarifah Mardiah; Munisa Munisa (Departement of Mathematics Education, 2024)
This research aims to analyze the internalization of values related to manners in eating and drinking among early childhood through Islamic cartoon animations at RA El Syarifah in Medan. The research method employed is qualitative descriptive. Data were collected through observation, interviews, and documentation, with data analysis using the steps of collection, reduction, presentation, and drawing conclusions. The results indicate that the introduction of Islamic manners through cartoon animations is effective in shaping religious character in early childhood. This process occurs not only during the imparting of knowledge but also through the exemplary role of teachers and daily practices of eating and drinking in accordance with manners. Consistency in applying moral values related to eating and drinking manners is a key factor in shaping religious character, and examples provided by teachers play a crucial role. Mealtime is identified as an effective moment for early childhood to apply their knowledge, aligning with their cognitive developmental stages. The research concludes that religious character can be instilled from an early age through daily activities, particularly in eating and drinking, relying on Islamic teachings. In addition to knowledge, character formation also requires habits and guidance from teachers as role models. These results are expected to serve as a foundation for further research in the context of developing Islamic religious education for early childhood.